I Online Congress on Multidisciplinary Rehabilitation (REABILITAMULTI): Exploring Advances and Challenges in the Care of Autism and Disabilities - PROCEEDINGS - DE SOUZA FERREIRA, MIRLLY (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
The 1º ReabilitaMulti was an online conference held from October 2 to 5, 2024, with the theme "Exploring Advances and Challenges in Autism and Disability Care". The event brought together renowned professionals to discuss innovative clinical practices, offering a valuable educational experience for students and professionals in the areas of health, pedagogy, psychopedagogy and social work. Participants received a 60-hour certification, and the proceedings will be published in a recognized scientific journal.